Reflections on University Education in Uganda and the COVID-19 Pandemic Shock: Responses and Lessons Learned - Nawangwe, Barnabas; Muwagga, Anthony Mugagga; Buyinza, Mukadasi; Masagazi, Fred Masaazi (Alliance for African Partnership Perspectives, 2021)
The reflections in this article are drawn from a study “Investing in Data and Evidence to Inform Education Policy in Response to The New Normal Caused by Covid 19 Pandemic in Uganda.” The study investigated how the various education stakeholders fitted into “the new normal” in accordance to the tripartite university roles namely: Teaching and learning, research and Community engagements / networking. A multiple case study approach informed this largely qualitative inquiry. Online interviews, and documentary reviews were used to generate the study narratives. Data analysis followed a more descriptive approach of coding of key words, and phrases in order to pinpoint common responses. Using a reflective approach, the article answers the following questions: How did the various university stakeholders respond to the COVID-19 Pandemic lock down? Are African (Uganda Universities) in particular prepared to positively encounter or take advantage unforeseen shocks? What strategies can we suggest to mitigate the plethora of pedagogical challenges created by the COVID-19 Pandemic shock? What will be the future of University Education after the COVID-19 Pandemic lock down? The implication of the study finding is that there is need to re-evaluate education /university funding as well as the need to integrate blended pedagogy at levels of education in Uganda more especially at university level.
Keywords: COVID-19 Pandemic; Responses and Lessons Learnt; AAP African Universities